2021
DOI: 10.5489/cuaj.7232
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Canadian urology: Cohort analysis from the 2018 Canadian Urological Association census

Abstract: Introduction: Physician burnout is associated with medical error, patient dissatisfaction, and poorer physician health. Urologists have reported high levels of burnout and poor work-life integration compared with other physicians. Burnout rates among Canadian urologists has not been previously investigated. We aimed to establish the prevalence of Canadian urologist burnout and associated factors. Methods: In the 2018 Canadian Urological Association census, the Maslach Burnout Inventory questions were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…1 The authors performed a relevant and detailed clinical trial and should be commended for their study due to the lack of evidence regarding the real benefits of one laser source over the other in the clinical setting. As reported by the authors, the findings of the current study significantly differ from the recently published trial by Ulvik et al, 2 as well many preclinical studies, 3 showing superior efficiency of ablation with TFL (at equal energy and frequency settings) when using "painting" or popcorning techniques for stone dusting. That fuels the scientific debate on Ho:YAG vs TFL outcomes in the real-life scenario.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…1 The authors performed a relevant and detailed clinical trial and should be commended for their study due to the lack of evidence regarding the real benefits of one laser source over the other in the clinical setting. As reported by the authors, the findings of the current study significantly differ from the recently published trial by Ulvik et al, 2 as well many preclinical studies, 3 showing superior efficiency of ablation with TFL (at equal energy and frequency settings) when using "painting" or popcorning techniques for stone dusting. That fuels the scientific debate on Ho:YAG vs TFL outcomes in the real-life scenario.…”
contrasting
confidence: 99%
“…2 Furthermore, as Harris et al highlight, 1 burnout also interferes with our medical judgment and therefore puts at risk the well-being of our patients. 3 Although there have been many studies reporting the prevalence of burnout and its consequences for the health care system and health care workers, we should focus more on searching for solutions to this problem. The documentation of medical information in an extensive electronic health record (EHR) is a cause of burnout.…”
mentioning
confidence: 99%
“…Major contributors in this population were similar, including financial strain (51% rate of burnout), female gender (45%), and those <46 years old (43%). 23…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the onset of the COVID-19 pandemic, several studies had already reported elevated burnout levels amongst various groups of healthcare workers (e.g. , 4 ; 6 ; 25 ; 27 ; 30 . Globally, research showed that as the COVID-19 pandemic progressed, burnout continued to be a significant problem impacting healthcare workers 11 ; 15 , and in some cases had become present at higher rates than previously reported 17 .…”
Section: Introductionmentioning
confidence: 99%